Manajemen Pendidikan Karakter Di MTs Negeri 5 Kebumen (Pembiasaan, Keteladanan dan Karakter) - Siti Fatimah; Sulis Rokhmawanto; Ari Susilowati; Imam Satibi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2021)
This study is based on a phenomenon concerning the implementation of character education in MTs Negeri 5 Kebumen. As a madrassa located in a rural environment, precisely in Klirong sub-district, MTs Negeri 5 Kebumen has implemented character education based on Islamic teachings and is able to achieve quite resounding achievements, both academic and non-academic achievement. This study aims to find out the knowledge, commitment and action of students towards character education in MTs Negeri 5 Kebumen. This study is a type of qualitative descriptive research with phenomenological approach with research subjects at MTs Negeri 5 Kebumen. The data collection techniques used in this study are observation techniques, interviews and documentation studies. Data analysis technique using the miles and huberman model. The results of study: 1) students' understanding of character education programs and various activities containing character values at Mts Negeri 5 Kebumen, both intracurricular, extracurricular, habituation and spontaneity activities. 2) students have shown a strong commitment to character education at MTs Negeri 5 Kebumen,namely by the willingness of students to make promises to comply with all applicable regulations in madrasas and are ready to get sanctions if they violate. 3) students have shownactions that reflect character values at MTs Negeri 5 Kebumen such as using good words, attitudes and actions.